Population biology and fishery characteristics of the smooth-hound Mustelus schmitti in Anegada Bay, Argentina - Colautti, Dario César (2010)
The smooth-hound Mustelus schmitti is a commercially important and common target shark inhabiting the southwestern Atlantic coastal system and is usually found in shallow waters. Using experimental and artisanal fishing records, we assessed seasonal biological and demographic characteristics related to fishing of the smooth-hound and its potential impact on this species. We found that after birth, juveniles remain in Anegada Bay until sexual maturity. The young adults mate in spring and then leave the bay in summer. The older adults come back to the bay in early spring to give birth, and mate and finally return to the open sea in late spring. This pattern suggests that the bay acts as a seasonal nursery and reproductive area. This species represents 95% of the fishery captures in this bay, although the fishery is highly seasonal. The average harvest during the years 2003-2008 was 164. tons, which represented only 2% of the total Argentinean smooth-hound landings. Fishing effort in the bay can be considered moderate due to the narrow time window and the use of selective gear that prevents the capture of juveniles. Future research should be directed at developing management plans at a broader regional scale to allow the recovery of M. schmitti stocks under heavy fishing pressure in other fishing areas.